Performance and key issues of 5G multi-channel joint transceiver technology - Yi PAN; Huihui LI; Lei ZENG; Weiwen CAI (Dianxin kexue)
With the explosive growth of data services,5G indoor coverage has become the top priority.Deploying 5G indoor subsystem is one of the important means to solve the problem of 5G indoor coverage.An upgrading scheme of 5G indoor subsystem based on multi-channel transceiver technology was introduced.This scheme can achieve double flow with single feeder and four flow with double feeder,and improve the performance of 5G with low cost.The main construction of the scheme includes:adding shaft cable,adding combiner,adding coupler,without changing the flat floor network structure.